LATE ROMAN POTTERY IN THE POTENZA VALLEY : First results regarding late Roman Potentia (Porto Recanati, Marche, Italy) - Verreyke, Hélène (Rei Cretariae Romanae Fautorum Acta, 2024)
In this article I would like to present the first results regarding the analysis of the late antique pottery from the Potenza Valley and in particular from the Roman town Potentia (Porto Recanati, Marche). Since 2002 the Potenza Valley survey-team has been active in the lower Potenza Valley, under the direction of F. Vermeulen of Ghent University (Belgium). The aim of this interdisciplinary project was to study the urban and rural occupation patterns in the Potenza Valley.